New data on the subgenus Gnathopaederus of the genus Paederus (Coleoptera: Staphylinidae: Paederinae) of mainland China - Peng, Zhong; Li, Qi-Li; Li, Li-Zhen; Gu, Fu-Kang (Zootaxa, 2015)
Paederus (Gnathopaederus) xuei Peng & Li sp. n. (Yunnan: Dawei Shan) and P. (G.) cheni Peng & Li sp. n. (Hunan: Badagong Shan) are described and illustrated. Additional records of P. (G.) bursavacua Willers, 2001, P. (G.) szechuanus (Chapin, 1927) and P. (G.) yunnanensis Willers, 2001 are reported.